What are the Challenges in Designing An Effective Personal Income Tax System? - Raeni Raeni; Astika Sari (Institute for Economic and Social Research, 2016)
This article aims to examine the challenges of designing individual’s income tax systems in general and particularly to observe taxpayers’ behaviour in developing countries. This study used case study approach to gain in depth understanding type of taxpayers’ attitude towards personal income tax systems. Based on the analyses, tax behaviour, which comprises the perception of fairness and motivation to comply, attracts urgent challenges in designing effective tax on personal income in every country and mainly underdeveloped countries. Every human being in each country has their social pattern towards tax policy. When the individual perception of fairness is significant, it will harmonise the ’client and service approach’ between taxpayers and governments. This condition would influence tax morale of individuals to comply with the policy and achieve high compliance rate. Therefore, it has argued that personal view of fairness and their motivation to comply with tax systems are becoming vital challenges in designing the tax policy on individual income. AbstrakArtikel ini bertujuan untuk menginvestigasi tantangan-tantangan yang dihadapi dalam merancang sistem perpajakan untuk wajib pajak orang pribadi dan secara khusus menganalisa perilaku wajib pajak di negara-negara berkembang. Penelitian ini menggunakan pendekatan studi literatur untuk mendapatkan secara mendalam jenis perilaku wajib pajak penghasilan orang pribadi. Berdasarkan hasil analisis terkait perilaku pajak, yang terdiri dari persepsi keadilan dan motivasi untuk mematuhi memberikan tantangan tersendiri dalam merancang pajak yang berlaku atas penghasilan pribadi di setiap negara dan terutama negara-negara berkembang. Setiap individu memiliki pola yang berbeda ketika berinteraksi terhadap kebijakan pajak. Ketika persepsi individu terhadap keadilan adalah signifikan, hal itu akan menyelaraskan pendekatan ’client and service’ antara pembayar pajak dan pemerintah. Kondisi ini akan memengaruhi semangat individu untuk mematuhi kebijakan dan mencapai tingkat kepatuhan yang tinggi. Oleh karena itu, asumsi bahwa pandangan individu terhadap keadilan dan motivasi untuk mematuhi sistem pajak menjadi tantangan penting dalam merancang kebijakan terhadap wajib pajak orang pribadi.Kata kunci: Pajak Penghasilan Orang Pribadi; Prinsip Keadilan; Moral Wajib PajakJEL classifications: E63